Neutrophil gelatinase-associated lipocalin as an early diagnostic biomarker of acute kidney injury in snake bite - Subramanian Senthilkumaran (Journal of Emergencies, Trauma and Shock, 2019)
Background: Snakebite envenomation is a major public health problem in the developing world, and the effects of viper envenomation on renal tissues leading to acute kidney injury (AKI) are well known. However, the usefulness of neutrophil gelatinase-associated lipocalin (NGAL) as a biomarker to detect AKI in viper envenomation cases were not studied much. Aims and Objectives: The present study was undertaken to find out plasma NGAL levels and assess its usefulness among the hospitalized Viperidae group of snakebite victims in predicting acute kidney injury. Materials and Methods: The plasma NGAL level was estimated within 6–8 h of all the 184 cases of viper bites along with other laboratory parameters. Results: It was elevated much before the elevation of serum creatinine levels, irrespective of the age, gender, and bite to hospital time. The sensitivity and specificity was 99.37 and 96.15, respectively. Elevated plasma NGAL levels in viper bite helped not only to detect AKI early but also assisted to plan for appropriate intervention. Conclusion: It is suggested to include estimation of plasma NGAL in the point of care testing, especially in emergency settings handling snakebite cases. However, more studies are recommended to find out its serial levels in snakebite cases following different kinds of snake envenomation with different clinical and laboratory manifestations in different age groups and gender belonging to different population so as to arrive at valid conclusions.